Facing the planetary : entangled humanism and the politics of swarming - Connolly, William E. (Duke University Press, 2017)
William E. Connolly expands his influential work on democratic pluralism to confront the perils of climate change by calling on us to deepen our attachment to the planet and to create a worldwide coalition of people from all demographics to contest the forces that prevent us from addressing climate change.